(3GdhSjW aj bVGA GdEdZGA (B:s (3OQGSI ebGQfI eOYeI HJWHjbGJ bVGFjI MOjKI aj cd ef GdLRGFQ(B-(3aQfSG(B-(3JhfS(B-(3eUQ (B= The mediator in revocation Judiciary : a comparative study supported by recent judicial applications in Algeria, France, Tunisia, and Egypt /s - (3HhVjGa, YeGQ,s 1960- ((3YeGf, GdCQOf (B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY,s, 2011)
(3jJfGhd GdcJGH Ef GdOYhi JYO Cge hSjdI bGfhfjI ddeMGaXI Ydi eHOC eTQhYjI GdCYeGd GdEOGQjI, hHhGSWJgG jJecf GdbGVj GdEOGQj ef HSW QbGHJg Ydi LgI GdEOGQI ShGA cGfJ EOGQI eQcRjI Ch eMdjI Ch eQabG YGeG(B. (3hMSHfG GdETGQI Cf TYGQ OhdI GdbGfhf dG jecf JLSjOg aj CQV GdhGbY EdG ef NdGd OYhi GdEdZGA, aYf WQjbgG jecf GdGSJgOGA Edi MbjbI bGfhfjI Cf eNJda bQGQGJ GdEOGQI jecf EdZGDgG ef LGfH GdbVGA GdeNJU aj MGd JLGhR EWGQ GdeTQhYjI(B. (3hHeeGQSI gPg GdQbGHI GdbVGFjI JLHQ GdEOGQI cTNU ef CTNGU GdbGfhf Ydi GdGdJRGe HbhGYOg hGMJQGe Mbhb GdCaQGO hMQjGJge(B. (3hgh eG ejR GdfXe GdbGfhfjI GdeYGUQI, Ef CgejI OYhi GdEdZGA JROGO OQLI EPG hVYfG HYjf GdGYJHGQ aFI GdehXajf GdYGedjf aj GdhRGQGJ hGdeMGaXGJ Ch GdhdGjGJ hGdHdOjGJ hSGFQ GdCLgRI GdEOGQjI, Pdc Cf GdeQcR GdbGfhfj dgDdGA LejYG hYdGbJge HGdgjFI GdeSJNOeI jJMOO GfWdGbG ef GdbQGQ GdEOGQj, ShGA JLSO GdbQGQ eKdG aj bQGQ JYjjf Ch EMGdI Ydi GdGSJjOGY Ch GfJOGH Ch bQGQ JCOjHj Ch bQGQ JQbjI hZjQgG ef GdbQGQGJ cKjQ, hdG jedc GdehXa Ef QZH aj EYOGe GdbQGQ GdEOGQj GdPj eS eQcRg GdbGfhfj, EdG GJHGY hSjdI OYhi GdEdZGA HgOa EHWGd eaYhd GdbQGQ GdeWYhf ajg(B. s
(3JUeje hEfJGL (B: (3ecJH OGQ GdKbGaI ddJUeje hGdEfJGL(B.s
(3HHdjhLQGajI (B: (3UaMI (B335-366. s
Keywords: (3bVGA GdEdZGAs -- (3aQfSGs; (3bVGA GdEdZGAs -- (3GdLRGFQs; (3bVGA GdEdZGAs -- (3eUQs